Propiedades Eléctricas en Membranas de Complejos Electrolitos Poliméricos PVA-OH/LI2SO4/PEG400 - Arbey Villegas, Edgar; Humberto Castillo, Jose; Bueno, Paulo Roberto [UNESP] (Assoc Brasil Polimeros, 2014)
Lithium ion conducting polymer electrolytes based on polyvinyl Alcohol (PVA-OH) complexed with salt Li2SO4 and different weight percent ratios of PEG(400) plasticizer have been prepared by solution cast technique using deionized water as solvent. The thermogravimetric analysis (TGA) showed that the thermal stability of the materials depended on the plasticizer content. The FTIR study confirmed the polymer salt complex formation. The modulus spectra indicated the non-Debye nature of the material; a dominant relaxation process is visible being associated with the dynamic glass transition, relaxation-a. The maximum of each peak is shifted to higher frequencies as the plasticizer increases due to an enhancement of dipolar mobility in the origin of cooperative motions. A power law frequency dependence of the real part of the electrical conductivity is observed, which is characteristic of the effects of ion-ion and/or ion-chain correlations in ion motion. This variation is well fitted to a Jonscher's expression.
Electrical Properties of Membranes Made with Polymer Electrolyte Complexes PVA-OH/LI2SO4/PEG(400)
Keywords: Electrical relaxation; ionic conductivity; glass transition; lithium ion batteries